Aerobic And Anaerobic Capacity Analysis Of Rowing Rowers Using Wattbike And Rowing Ergometer Concept II - Alfy Fauzia Azmi; Amung Ma’mun; Boyke Mulyana (UNIVERSITAS NEGERI MAKASSAR, 2022)
The purpose of this study was to determine